Prediksi Klasemen Akhir Kompetisi Sepakbola Indonesia Menggunakan Metode Perluasan Ekspektasi Phytagoras - Aceng Komarudin Mutaqin; Yhupi Praga Adri (Department of Statistics, Syiah Kuala University, 2019)
Makalah ini menerapkan metode perluasan ekspektasi Phytagoras pada data hasil pertandingan kompetisi sepak bola Liga Indonesia untuk memprediksi klasemen akhir kompetisi. Jumlah gol memasukan dan jumlah gol kemasukan dalam suatu pertandingan dari suatu tim selama satu musim kompetisi dimodelkan sebagai peubah acak yang berdistribusi Poisson. Dalam makalah ini data yang digunakan adalah data hasil pertandingan kompetisi sepakbola Indonesia Super League (ISL) tahun 2013. Hasil pengolahan data menunjukkan bahwa metode perluasan ekspektasi Phytagoras dengan asumsi distribusi Poisson mampu mengelompokkan dengan baik ranking dari tim peserta kompetisi ISL 2013. This paper applies the method of extending Pythagoras’ expectations to the results of the matches of the Indonesian League soccer competition to predict the final standings of the competition. The number of goals entered and the number of goals conceded in a match from a team for one season is modeled as a random variable with Poisson distribution. In this paper the data used is data on the results of the 2013 Indonesia Super League (ISL) soccer competition. The results of data processing showed that the method of expansion of Pythagoras’ expectations assuming the Poisson distribution was able to classify the ranking of participants of the ISL 2013 competition well. The team whose performance exceeds expectations is the PERSELA Team. While the team whose performance is below expectations is the SRIWIJAYA Team.